2014
DOI: 10.1161/strokeaha.114.007095
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Tada Formula With Software Slicer

Abstract: Background and Purpose— The Tada (ABC/2) formula has been used widely for volume assessment of intracerebral hematoma. However, the formula is crude for irregularly shaped hematoma. We aimed to compare the accuracy of the ABC/2 formula with open source software Slicer. Methods— Computed tomographic images of 294 patients with spontaneous intracerebral hematoma were collected. Hematoma volumes were assessed with the ABC/2 formula and calculated with soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 15 publications
1
33
0
Order By: Relevance
“…22,23 It is also wellacknowledged that ABC/2 tends to overestimate lesion volumes. 24,25 In our study, ABC/2 overestimated ICH volume by 45%, on average. While the mean SegTool measurements were .…”
Section: Discussionsupporting
confidence: 46%
“…22,23 It is also wellacknowledged that ABC/2 tends to overestimate lesion volumes. 24,25 In our study, ABC/2 overestimated ICH volume by 45%, on average. While the mean SegTool measurements were .…”
Section: Discussionsupporting
confidence: 46%
“…13,15,21 Especially in larger hematomas, we observed disagreement between raters as well as systematic volume overestimation by 30% on average ( Figure 2B). In 2 trials evaluating the benefit of surgery versus initial conservative treatment in ICH, larger and superficial hematomas were significantly more likely to cross over and receive surgery, despite initial randomization to conservative treatment.…”
Section: Discussionmentioning
confidence: 87%
“…Whilst some researchers have found that the ABC/2 method overestimates lesion volume compared to computer-assisted methods [39, 44, 45, 47, 51–55], others claim the opposite [41, 56]. Haemorrhagic lesions that have a regular shape are more accurately estimated using the ABC/2 method compared to lesions with irregular or multi-lobular shapes [43, 4556].…”
Section: Methodsmentioning
confidence: 99%